Merangkul Bumi Menurut Ajaran Paus Fransiskus - Nicolas Febriso Naibaho; Martina Rosmaulina Marbun (Journal New Light, 2025)
The ecological crisis gripping the world is increasingly apparent through the intensity of natural disasters, extreme climate change, and environmental degradation that threaten human survival. In response to this situation, Pope Francis, in his encyclical Laudato Si' (2015), called on all humanity to view the earth as a shared home that must be cared for with full responsibility. This article focuses on the relevance of Pope Francis' teachings in facing today's ecological challenges, emphasizing the development of ecological spirituality, the concept of integral ecology, and an awareness of social responsibility. The study was conducted through a literature review by examining encyclicals, official documents of the Catholic Church, and recent Indonesian-language books and academic articles. The results show that caring for the earth is not merely a technical act of conservation, but is a call to shift the paradigm of life to align with faith, science, and social solidarity. The Catholic Church itself plays a crucial role in building ecological awareness through education, liturgy, and interfaith dialogue. By integrating moral, spiritual, and public policy aspects, the concept of integral ecology offered by Pope Francis is seen as highly relevant to addressing the challenges of the global environmental crisis. This article emphasizes that the commitment to embracing the earth is not just an ecological obligation, but also a call of faith and humanity for the sake of the sustainability of life for current and future generations.